Application of Gluten and Casein Free Diet Patterns Through Augmented Reality Pop Up Book and Nutri-App Media in SLB Negeri Semarang - Ilham Muhammad; Beni Rifqi Yafi Hibatullah; Nurul Afifah Dwifitriana; Muhammad Hakam Amnan; Farhan Syafiq Fadhillah (Privietlab, 2021)
Autism is a brain function disorder that causes impaired communication and social interaction. One of the obstacles experienced by autistic children in SLB Negeri Semarang is the difficulty of accepting new foods, because they are picky eaters. This condition results in the prevalence of malnutrition and micronutrient deficiencies in autistic children, because there is little variation in food or only dominant in certain foods. The purpose of this study was to implement a casein and gluten-free diet program (CFGF) with Augmented Reality Pop Up Book and Nutri-App in SLB Negeri Semarang.The method used is an assessment to find out the benefits after the counseling, training, and mentoring that have been carried out. The results obtained are that there is a change in the autistic children of SLB Negeri Semarang which has a rating of 4.67 out of 5 with a description of 67% of respondents giving a rating of 5 and 33% giving a rating of 4. In addition, 75% of respondents gave a score of 5 (excellent) about the importance of a diet program for autistic children conducted by researchers. In conclusion, the program brought by the researcher can increase understanding of the CFGF dietary in SLB Negeri Semarang.